1984
DOI: 10.1111/j.1744-7348.1984.tb03085.x
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation studies in relation to the storage of Araucaria seed

Abstract: S U M M A R YRelationships between seed moisture content (fresh weight basis) and germination were examined for nine Araucaria species by desiccation under mild environmental conditions. The lowest safe moisture content, below which germination percentage begins to decline, was estimated in each case. Seeds can be grouped into three moisture content categories: the first group (including A. araucana, A. angustifolia, A. hunsteinii and A. bidwillii) cannot be safely dried to below 25-40%; the second group (incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
4

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 3 publications
1
35
0
4
Order By: Relevance
“…Além da classificação fisiológica do comportamento das sementes durante a dessecação e no armazenamento, a origem, ocorrência (Roberts, 1973;Roberts e King, 1980;Bonner, 1990;Pammenter e Berjak, 2000), tipo de fruto, semente (Hong et al, 1996), classificação taxonômica (Hong et al, 1996), conteúdo de água no ponto de maturidade fisiológica (Hong et al, 1996e Davide et al, 2001, tamanho da semente e a combinação destas (Tompset, 1984), são características propostas para permitir o melhor entendimento das respostas fisiológicas e ecologia das espécies.…”
Section: Introductionunclassified
“…Além da classificação fisiológica do comportamento das sementes durante a dessecação e no armazenamento, a origem, ocorrência (Roberts, 1973;Roberts e King, 1980;Bonner, 1990;Pammenter e Berjak, 2000), tipo de fruto, semente (Hong et al, 1996), classificação taxonômica (Hong et al, 1996), conteúdo de água no ponto de maturidade fisiológica (Hong et al, 1996e Davide et al, 2001, tamanho da semente e a combinação destas (Tompset, 1984), são características propostas para permitir o melhor entendimento das respostas fisiológicas e ecologia das espécies.…”
Section: Introductionunclassified
“…Moreover, seed storage behaviour may difTer among species within a genus. For example, Tompsett (1982Tompsett ( , 1984 has shown that the large fleshy seeds of the species of Araucaria from South America are recalcitrant, whereas the smaller seeds of many Araucaria species from the Western Pacific are orthodox.…”
Section: Introductionmentioning
confidence: 99%
“…Further desiccation leads to a quick reduction of viability. The point at which a rapid drop of viability starts to be observed is termed the 'critical moisture content' (King and Roberts, 1979) or 'lowest safe moisture content' (Tompsett, 1984). The point where viability is completely lost is called 'lethal moisture content ' (Hong and Ellis, 1992).…”
Section: G H 2 O (G Dry Matter)mentioning
confidence: 99%